'Maranga Ake Ai' The Heroics of Constitutionalising Te Tiriti O Waitangi/The Treaty of Waitangi in Aotearoa New Zealand. (December 2020) - Ruru, Jacinta; Kohu-Morris, Jacobi
In 1840, some of the sovereign nations of Māori signed te Tiriti o Waitangi (the Māori language version of the Treaty of Waitangi) with the British Crown. Hone Heke was the first Māori leader of the northern nation of Ngāpuhi to sign, but by 1844 he was leading a significant revolt against British colonialism in Aotearoa New Zealand by chopping down British flagpoles erected on his lands. While Māori may have initially welcomed the intent of te Tiriti as a means for seeking British help to protect their international borders, the British prioritised the English version of the Treaty which recorded the transfer of sovereignty from Māori to the British. As the British transposed their dominant legal traditions of governance, including bringing to the fore their doctrine of parliamentary supremacy, Māori have been seeking their survival ever since. We extend this by focusing on why the doctrine of parliamentary sovereignty needs to adapt to the Treaty's promise of bicultural power sharing.